Inhibition of sperm motility in male macaques with EP055, a potential non-hormonal male contraceptive - O’Rand, Michael G.; Hamil, Katherine G.; Adevai, Tiffany; Zelinski, Mary (PLOS ONE, 2018)
Abstract Men have two practical choices for contraception; the condom which has a high typical use failure rate or vasectomy. New male hormonal and non-hormonal contraceptives are under development that target either the production of sperm (spermatogenesis) or the delivery of sperm. One particular target is the sperm protein EPPIN, which is present on the surface of human spermatozoa. EP055 is a small organic compound that targets EPPIN on the surface of sperm and inhibits motility. EP055 was tested in cynomolgus (Macaca fascicularis) males to determine its plasma half-life after intravenous (i.v.) infusion of a single dose and for binding to its target tissues. Our initial study demonstrated a plasma half-life for EP055 of 10.6 minutes. In a second study examination of macaque testis, epididymis, and plasma after i.v. infusion of a single dose of compound EP055 (63.25 mg/kg) demonstrated that EP055 was detected in testis and epididymis two hours and six hours post-infusion. We initiated a trial in rhesus (Macaca mulatta) males to assess the availability of EP055 in semen and its effect on sperm motility as a measure of the drug's efficacy. Four macaques were infused with a low dose (75–80 mg/kg) followed by a recovery period and a subsequent high dose (125–130 mg/kg) of EP055. After high dose administration, sperm motility fell to approximately 20% of pretreatment levels within 6 hours post-infusion; no normal motility was observed at 30 hours post-infusion. Recovery of sperm motility was obvious by 78 hours post-infusion; with full recovery in all animals by 18 days post-infusion. EP055 has the potential to be a male contraceptive that would provide a reversible, short-lived pharmacological alternative.